Essays on health at birth, financial literacy and educational outcomes - Furtado, Isabela Brandão (2018)
This thesis consists of three essays related to microeconomics applied to health and education. The first chapter analyses a large-scale experimental impact evaluation of a financial education pilot program for students from public primary schools in two Brazilian cities. The second chapter estimates effects of birth weight on health and educational outcomes using a twin fixed effect approach for Brazil, using a matching of administrative records of birth and school enrollment. The third chapter explores the effects of prenatal exposure to a violent environment on birth weight and investigates whether the in-utero and early life violence shocks can have further impacts, particularly on schooling accumulation.